2018
DOI: 10.4103/aer.aer_64_18
|View full text |Cite
|
Sign up to set email alerts
|

A study to compare the analgesic efficacy of dexmedetomidine and fentanyl as adjuvants to levobupivacaine in ultrasound-guided supraclavicular brachial plexus block

Abstract: Background:Supraclavicular brachial plexus provides complete and reliable anesthesia for upper limb surgeries. Adjuvants are added to local anesthetists to improve various block characteristics. There are limited studies comparing the efficacy of dexmedetomidine and fentanyl as an adjuvant to levobupivacaine.Aims:The aim of the study was to evaluate and compare the effect of dexmedetomidine versus fentanyl as an adjuvant with levobupivacaine in ultrasound-guided supraclavicular brachial plexus block.Settings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The incidence of bradycardia and hypotension was described in 28 studies [ 23 , 34 37 , 39 – 42 , 45 , 47 , 48 , 51 – 53 , 58 , 61 , 63 , 64 , 66 , 67 , 69 , 78 – 80 , 83 – 85 ] and 26 studies [ 23 , 34 – 36 , 39 – 42 , 45 48 , 51 – 53 , 58 , 63 , 64 , 66 , 67 , 69 , 78 – 80 , 84 , 85 ] respectively. Pooled analysis showed that perineural DEX>60 μg increased the risk of bradycardia (risk difference [RD]: 0.16, 95% CI: 0.06 to 0.26, I 2 = 97%, P = 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of bradycardia and hypotension was described in 28 studies [ 23 , 34 37 , 39 – 42 , 45 , 47 , 48 , 51 – 53 , 58 , 61 , 63 , 64 , 66 , 67 , 69 , 78 – 80 , 83 – 85 ] and 26 studies [ 23 , 34 – 36 , 39 – 42 , 45 48 , 51 – 53 , 58 , 63 , 64 , 66 , 67 , 69 , 78 – 80 , 84 , 85 ] respectively. Pooled analysis showed that perineural DEX>60 μg increased the risk of bradycardia (risk difference [RD]: 0.16, 95% CI: 0.06 to 0.26, I 2 = 97%, P = 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 605 articles were excluded as they were not relevant to the review. Twenty-four articles were selected for full-text review of which 12 RCTs fulfilled the inclusion criteria [ 19 30 ]. A total of 12 studies were excluded with reasons (2 studies were not RCTs, 4 studies had no control group, and 6 studies were not on fentanyl).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that addition of 0.75 μg/kg dexmedetomidine to 0.5% levobupivacaine for supraclavicular plexus block shortens sensory and motor block onset time and extends sensory block, motor block, and analgesia duration. Kaur M et al [8] evaluated and compared the effect of dexmedetomidine versus fentanyl as an adjuvant with levobupivacaine in ultrasound-guided supraclavicular brachial plexus block. This study design was a prospective, randomized, double-blind controlled study.…”
Section: Discussionmentioning
confidence: 99%